1996
DOI: 10.1016/s0168-1702(96)01398-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and distribution of the receptors for coxsackievirus B3 during fetal development of the Balb/c mouse and of their brain cells in culture

Abstract: This study was designed mainly to determine the relationships between the expression and distribution of the cellular receptor proteins for coxsackievirus B3 (CVB3) and susceptibility of mouse brain cells during fetal development of Balb/c mice. Immunoblot analysis of fetal extracts demonstrated that the CVB3 receptor proteins were first expressed at day 14 of the fetal stage, and that maximal expression of the cellular receptor occurred at near term or newborn stage. Results also suggested that newborn mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In agreement with previous studies (Xu and Crowell, 1996;Honda et al, 2000), we detected CAR on all neural cells in sections of the retina. However, CAR was enriched at specific sites, including a strong localization on RGC axons facing the vitreous body, suggesting that CAR might mediate an interaction of RGC axons with ECM proteins of the inner limiting membrane, or with other RGC axons.…”
Section: Car Localization In the Developing Retina Is Dynamically Regsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous studies (Xu and Crowell, 1996;Honda et al, 2000), we detected CAR on all neural cells in sections of the retina. However, CAR was enriched at specific sites, including a strong localization on RGC axons facing the vitreous body, suggesting that CAR might mediate an interaction of RGC axons with ECM proteins of the inner limiting membrane, or with other RGC axons.…”
Section: Car Localization In the Developing Retina Is Dynamically Regsupporting
confidence: 93%
“…In the adult heart, CAR is predominantly localized at the intercalated discs (Shaw et al, 2004). In the vertebrate nervous system, CAR is strongly expressed during embryogenesis, followed by drastic reduction at early postnatal stages (Xu and Crowell, 1996;Honda et al, 2000;Dorner et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 How this role is subverted during malignant progression is unknown, but to associate CAR with the 'differentiated state' (because it is an epithelial adhesion molecule in polarized epithelia) is likely incomplete, or incorrect. To suggest that CAR functions solely as a mediator of barrier function in polarized epithelia also does not appear to be consistent with its emerging portrait as a developmentally expressed adhesion molecule in the mammalian brain, [69][70][71] heart, 8,72,73 and skeletal muscle, 74 nor with its characterization as a mediator of heterotypic cell interactions. 10,68 The fact that CAR is ubiquitously expressed in both epithelium-and mesenchyme-derived tissues (apparently including hematopoietic precursors 53 ) during development suggests a more generalized role for CAR.…”
Section: Discussionmentioning
confidence: 95%
“…In an effort to develop an alternative model for the study of VZV infection, newborn rats were tested as they have been reported to be far more susceptible than adult rats to infection with HSV [Tanaka and Southam, 1965] or coxsackie viruses [Xu and Cromwell, 1996]. In addition, human infants born to mothers who experience varicella during pregnancy [Brunell and Kotchmar, 1981] or infants who get varicella during the first month of life [Baba et al, 1986] often develop zoster in early life, suggesting that latency may be more readily established in newborns.…”
Section: Introductionmentioning
confidence: 99%